New methodological approach and analysis quantification of fiscal revenues from collection of environmental taxes - Munitlak-Ivanović, Olja (Ekonomski pogledi, 2014)
Subject of researche was to analyze the existing ways of measuring the financial effects of environmental taxes in the EU as a percentage of GDP and on the basis of the collected revenue - 'GDP-based methodology' and a new calculation model ('per capita based methodology'). The aim of the research is a comparative analysis of existing GDP-based method and the new per capita based method of quantifying the financial impact of environmental taxes in the EU region. The main hypothesis is that there is a significant disproportionality in the results of measurements depending upon the method of calculation. Derived hypothesis that the newly proposed method less discriminatory because it takes into account the number of inhabitants and still insisting on harmonization of legislation in this area is not desirable or necessary.